2016
DOI: 10.1007/s10875-016-0281-6
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Splice Site Mutations in PIK3R1 Cause Hyper IgM Syndrome, Lymphadenopathy and Short Stature

Abstract: The purpose of this research was to use next generation sequencing to identify mutations in patients with primary immunodeficiency diseases whose pathogenic gene mutations had not been identified. Remarkably, four unrelated patients were found by next generation sequencing to have the same heterozygous mutation in an essential donor splice site of PIK3R1 (NM_181523.2:c.1425 + 1G > A) found in three prior reports. All four had the Hyper IgM syndrome, lymphadenopathy and short stature, and one also had SHORT syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 32 publications
(47 reference statements)
2
41
0
Order By: Relevance
“…These previous mutations all lead to upregulated PI3K activity, however, mutations and truncations in both the iSH2 and cSH2 have been discovered that downregulate PI3K activity through decreased sensitivity to insulin signalling. These mutations cause SHORT syndrome (Short stature, hyper-extensibility, hernia, ocular depression, Rieger anomaly, and teething delay) (Chudasama et al, 2013;Dyment et al, 2013;Huang-Doran et al, 2016;Petrovski et al, 2016;Schroeder et al, 2014;Thauvin-Robinet et al, 2013), with the most common mutation disrupting the phosphotyrosine binding site in the cSH2 domain (R649W). We have characterised the molecular mechanism of activation of a C-terminal truncation of p85α (Q572*) and a point mutant in the cSH2 (R649W) that disrupts phosphorylated tyrosine binding leading to impaired insulin signalling.…”
Section: Discussionmentioning
confidence: 99%
“…These previous mutations all lead to upregulated PI3K activity, however, mutations and truncations in both the iSH2 and cSH2 have been discovered that downregulate PI3K activity through decreased sensitivity to insulin signalling. These mutations cause SHORT syndrome (Short stature, hyper-extensibility, hernia, ocular depression, Rieger anomaly, and teething delay) (Chudasama et al, 2013;Dyment et al, 2013;Huang-Doran et al, 2016;Petrovski et al, 2016;Schroeder et al, 2014;Thauvin-Robinet et al, 2013), with the most common mutation disrupting the phosphotyrosine binding site in the cSH2 domain (R649W). We have characterised the molecular mechanism of activation of a C-terminal truncation of p85α (Q572*) and a point mutant in the cSH2 (R649W) that disrupts phosphorylated tyrosine binding leading to impaired insulin signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a number of additional studies have identified APDS patients with mutations in PIK3CD 5, 7, 6469 or PIK3R1 6, 7073. Patients with GOF mutations in either of these genes appear to largely phenocopy each other, despite the fact that p85α is ubiquitously expressed and can pair with p110α and p110β in addition to p110δ.…”
Section: Alterations In Pi3kδ Signalling Leads To Pids In Humansmentioning
confidence: 99%
“…Growth retardation is common in patients with APDS2 6, 73, 74 but does not seem to be a feature of APDS1 and may relate to the association of heterozygous mutations in PIK3R1 with SHORT syndrome (short stature, hyperextensibility of joints, hernia, ocular depression, Rieger anomaly and teething delay)8891.…”
Section: Clinical Features Of Apdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole exome sequencing (WES) was performed in 5 cases (P6 died before). Since mutations in PIK3CD or PIK3R1 genes have been recently reported as responsible for novel PIDs characterized by elevated IgM, normal/low IgG levels, lymphopenia, respiratory infections, lymph node enlargement, and elevated risk of lymphomas [26][27][28][29][30], these genes were analyzed by direct sequencing. Variants in causative or potential candidate genes identified through WES were confirmed through Sanger sequencing.…”
Section: Whole Exome and Sanger Sequencingmentioning
confidence: 99%